Jews and race: writings on identity and difference, 1880 - 1940 - Hart, Mitchell Bryan (The Tauber Institute series for the study of European Jewry, 2011)
I. Jews as a race: overview -- II. Anthropology -- III. Medicine and biology -- IV. Society and economy -- V. Racial mixing: intermarriage and conversion -- VI. Politics, polemics, and apologetics